Tales of Soils: Get Your Hands Dirty, but Make Yourself Brainy - Chiam Jing Tong; Danieal Zita; Muhammad Faqree Aiman Mahtar; Chee-Ming Chan; Salina Sani; Tuan Noor Hasanah Tuan Ismail (Penerbit UTHM, 2025)
Tales of Soils: Get Your Hands Dirty, but Make Yourself Brainy is a compilation of personal, heartwarming stories of self-discovery, learning and growth of student hailing from the SOIL Class, Semester 2 Session 2023/2024. The essays are arranged by sections: It starts with individual aspirations written at the beginning of the semester, followed by a collective group essay as closure at semester end. The stories tell of anxiety for the unchartered waters, worry for the unknown new knowledge base and excitement for the adventure in store, then threads through to the group reflections coming out of the journey after overcoming SOIL perils, EARTH ambush, and GROUND booby traps. We especially hope that future SOIL students would enjoy the book, and find something worthy to take with them on the earthy learning adventure. Happy reading